2008
DOI: 10.1007/s10669-008-9192-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of social desirability on self-reported environmental attitudes and ecological behaviour

Abstract: There are several claims in the literature that social desirability concerns affect people's response to selfreported measures of environmental attitudes and ecological behaviour. However, only a few empirical studies have indirectly evaluated the impact of social desirability on environmental issues measures, and those who did have found only a low impact. This article describes two studies that explicitly address whether socially desirable responding has direct and moderating effects on self-reported environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(126 citation statements)
references
References 37 publications
(39 reference statements)
6
120
0
Order By: Relevance
“…He interpreted this result as a hint that self-deception and not others deception was measured and that it was easier to adapt attitude as a consequence of perceived pressure due to SDB than to adapt behaviour. A similar pattern of social desirability effect in adults was found by Milfont (2009) who analysed psychology students in a study like ours, using different Preservation, Utilisation, and ecological behaviour measures as well as an impression management scale for adults.…”
Section: Impact Of Social Desirability On Environmental Values and Gebsupporting
confidence: 85%
See 2 more Smart Citations
“…He interpreted this result as a hint that self-deception and not others deception was measured and that it was easier to adapt attitude as a consequence of perceived pressure due to SDB than to adapt behaviour. A similar pattern of social desirability effect in adults was found by Milfont (2009) who analysed psychology students in a study like ours, using different Preservation, Utilisation, and ecological behaviour measures as well as an impression management scale for adults.…”
Section: Impact Of Social Desirability On Environmental Values and Gebsupporting
confidence: 85%
“…Neither a masking of the relationship between GEB and Utilisation by SDB nor any moderator effect of the Lie scores was found. That is, the impact of social desirability on ecological behaviour is the same for people with low, as well as high, agreement with Preservation or Utilisation items, which is consistent with Schahn (2002) as well as with Milfont (2009).…”
Section: Removing the Effects Of Sdb: Impact On The Attitude-behaviousupporting
confidence: 84%
See 1 more Smart Citation
“…Second, pro-environmental behavior and awareness were assessed using self-report measures, which are susceptible to effects of social desirability. Although it has been demonstrated that effects of social desirability on self-reported pro-environmental behavior and awareness are weak at most (Milfont, 2009), a more direct and implicit measure of pro-environmental behavior might have provided additional insights. It would therefore be interesting to further investigate the association of testosterone and cortisol with pro-environmental behavior in a laboratory or field setting where it is possible to directly observe different indicators of pro-environmental behavior such as donating, recycling, or consumer behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Chao et al [5] reported that there was a certain difference between self and other reporting in answering environmental behavior; he advised researchers to be careful in interpreting results of only self-reported behavior as these results are usually higher than the actual turnout. Kaiiser et al [6] and Milfont [7] assumed that social desirability is among the factors explaining the high attitude-behavior gap. They concluded that a socially-desirable response had only a weak direct effect on environmental attitudes and self-reported behaviors.…”
Section: Introductionmentioning
confidence: 99%